The Wnt signaling pathway: prospects for pharmacological regulation - V. V. Tatarskiy (Успехи молекулярной онкологии)
Wnt cascade is one of the most important signal pathways in the cell, which is required for normal embryonic development, differentiation, maintenance of stem cell phenotype and migration. Mutations in this pathway are associated with tumor growth (especially with colon cancers, hepatocarcinomas and leukemias), where they participate in maintenance of tumor-initiating cells and metastasing. Because of that there is a considerable interest to develop inhibitors of Wnt pathway as anti-tumor agent. But this inhibitors are still only in early stages of clinical investigations. In this article we review the main targets for this anti-cancer agents and their preclinical and clinical status.